PENGARUH EKOLITERASI PESERTA DIDIK MELALUI IMPLEMENTASI MODEL PROJECT-BASED LEARNING BERBANTUAN WEB BLOG PADA SISWA SEKOLAH DASAR - Lestari, Eunike Dwi; Atmojo, Idam Ragil Widianto; Daryanto, Joko (Universitas Bhinneka PGRI, 2025)
The ecoliteracy level of elementary school students remains relatively low, particularly in their ability to understand environmental issues critically and responsibly. This limitation indicates that students are not yet able to connect ecological concepts to real-life contexts in a comprehensive manner. This study aimed to examine the effectiveness of a web-blog-assisted Project-Based Learning (PjBL) model in enhancing the ecoliteracy of elementary school students. The research employed a quasi-experimental design and involved two fifth-grade classes from two different schools. The results indicated that students in the experimental group experienced a statistically significant improvement in ecoliteracy scores compared to those in the control group (p < 0.05; Hedges’s g = 0.78). The two-way ANOVA analysis further revealed a significant main effect of the learning model (p = 0.001), as well as a significant interaction between the learning model and classroom context (p = 0.008). Teachers observed that student involvement in project-based activities positively contributed to their environmental understanding and active engagement in learning processes. These findings suggest that the web-blog-assisted Project-Based Learning model is an effective and meaningful approach for improving students’ ecoliteracy in elementary education.